Context Ontology in Mobile Applications - Norki, Farhanah Atiqah; Mohamad, Radziah; Ibrahim, Noraini (Universiti Utara Malaysia Press, 2020)
Mobile applications are expected to receive context input Mobile applications are expected to receive context in put such as location, speech, and network from different context providers. Since context can be considered as knowledge, a formal method is needed to capture this knowledge. There is less work on ontology model that could be reused to model a new context ontology for Android mobile application. Therefore, this study proposed an ontology specifically for Android mobile application, COCCC, to formalize context knowledge present within it. METHONTOLOGY method was used to create COCCC ontology as it offers intermediate representation in the form of concepts. The concepts from the context ontology were extracted from various resources, sorted and categorized based on types and functions for standardization purposes. Survey was given to five domain experts for evaluation of COCCC ontology in terms of its usability. Data from these experts were analyzed and the results have confirmed that the proposed context ontology is usable to Android mobile application developers.